Bilateral single system ectopic ureters: Case report with literature review - Kumar A; Goyal N; Trivedi S; Dwivedi U; Singh P (African Journal of Paediatric Surgery, 2008)
Bilateral single system ureteral ectopia (BSSEU) is one of the rarest entities in urology, with less than 80 cases reported so far. Incontinence resulting from the underlying anomaly can be devastating to the child. It is generally agreed that suitable urinary continence and long dry intervals are seldom obtainable because of poorly developed trigone and bladder neck area. We herein report a case of BSSEU managed by bilateral ureteric reimplantation, achieving satisfactory continence and bladder capacity without the need for urinary diversion or bladder neck reconstruction.